(untitled) (Latakia University Journal -Basic Sciences Series, 2022)
The nucleus ,during fission, whether induced or spontaneous , performs amoebic movement that alternate between elongation and flattening , until a neck is formed in the form of congestion near the middle during the elongation period. Followed by relatively high probability of separating the two nuclei formed on both sides of the neck from each other , and this is accompanied by the emission of two or three neutrons ,which are actually the neutrons in the neck , this accident called nuclear fission. Induced fission can affect any nucleus , but with probability close to zero ,except for the nucleus of the natural isotope ,and the nuclei of a few transuranic isotopes ,the most important of them is that have the compound excitation energy ,that resulting from the absorption of thermal neutron is greater than by and have mass number .Heavy and medium nuclei are consisting of a core containing neutrons and protons , the neutrons within this core reduce electrical repulsion between the protons within it .the outer layer of the nucleus is an skin containing only neutrons ,the job of this neutron skin affect on that protons to confined them within the nucleus and prevented them from releasing because of the colonic repulsion, that subjected of it, which is greater than its binding energy when it located on the surface of the core. The neutron skin surrounding the fissile nucleus must be of sufficient degree of cohesion to not be interrupted by amoebic movements that precede fission ,and also flexible enough to allow these movements , and what determines these two things is the thickness and density of this skin ,and thus the mean binding energy for its neutrons .in this research ,an attempt is made to determine the density of the neutron skin surrounding the fissile nuclei , and then depend on that ,determine the relation between the parameters of this skin of thickness with each of A and Z for the fissile nuclei.There are reference methods to determining the thickness of the neutron skin surrounding the nucleus ,also the density within it , it will be determined in this work by calculating the length of the neck formed between the two nuclei that result from fission just before fission occurs in a method that was found in this work .